(3GdEMUGA GdESJOdGdj (B/s - (3WYeI, MSf jGSjfs; (3MfhT, EjeGf MSjf s ((3YeGf(B: s (3OGQ UaGA ddfTQ hGdJhRjY(B, s, 2010)
(3fXQjI GdeLehYGJ hWQb GdYO(B- (3eONd Gdi fXQjI GdEMJeGd(B- (3GdeJZjQGJ GdYThGFjI hJhRjYGJgG GdEMJeGdjI(B- (3CSdhH GdYjfGJ hWQb ENJjGQgG(B- (3GdeYGjfI GdEMUGFjI hJhRjYGJgG(B- (3fXQjI GdJbOjQ(B- (3ENJHGQ GdaQVjGJ GdEMUGFjI(B- (3GdENJHGQGJ GdeSJfOI Ydi GdJhRjY GdWHjYj(B- (3GdENJHGQGJ GdeSJfOI Ydi JhRjY(B- (3GdENJHGQGJ GdeSJfOI Ydi JhRjY eQHY cGj(B- (3GdENJHGQGJ GdeSJfOI Ydi JhRjYs
Keywords: (3GdEMUGA GdESJOdGdjs; (3GdEMUGA GdhUajs; (3GdESJOdGd GdEMUGFjs